Gender Effect on the Relationship between Talent Identification Tests and Later World Triathlon Series Performance - Alba Cuba-Dorado; Veronica Vleck; Tania Álvarez-Yates; Oscar Garcia-Garcia (MDPI AG, 2021)
Background: We examined the explanatory power of the Spanish triathlon talent identification (TID) tests for later World Triathlon Series (WTS)-level racing performance as a function of gender. Methods: Youth TID (100 m and 1000 m swimming and 400 m and 1000 m running) test performance times for when they were 14-19 years old, and WTS performance data up to the end of 2017, were obtained for 29 female and 24 male "successful" Spanish triathletes. The relationships between the athletes' test performances and their later best WTS ranking positions and performance times were modeled using multiple linear regression. Results: The swimming and running TID test data had greater explanatory power for best WTS ranking in the females and for best WTS position in the males (R2a = 0.34 and 0.37, respectively, p ≤ 0.009). The swimming TID times were better related to later race performance than were the running TID times. The predictive power of the TID tests for WTS performance was, however, low, irrespective of exercise mode and athlete gender. Conclusions: These results confirm that triathlon TID tests should not be based solely on swimming and running performance. Moreover, the predictive value of the individual tests within the Spanish TID battery is gender specific.